Gigi Tiruan Lengkap Resin Akrilik pada Pasien Full Edentulous - Hendri Andrian; Sri Oetami (Pusat Riset dan Inovasi Nasional, 2025)
Tooth loss in adulthood is a common problem, and the prevalence tends to increase with age. This condition can be caused by various factors, including tooth extraction due to extensive, unrestored caries, loose and loose teeth due to periodontal disease, a history of trauma to the dentoalveolar area, and systemic disorders such as diabetes mellitus and osteoporosis. If tooth loss is not promptly treated, it can cause various negative impacts, such as resorption or reduction of the alveolar bone in the edentulous area, impaired masticatory function, speech (phonetic) disorders, and can even affect temporomandibular joint (TMJ) function. This case report aims to implement treatment using complete dentures made of acrylic resin in a patient with a fully edentulous condition. The treatment process begins with an initial examination, jaw impressions, jaw occlusion registration, denture selection and placement, and post-fitting evaluation. The results of this case report indicate that the installation of complete dentures made of acrylic resin can restore three main functions of the oral cavity: mastication (chewing), phonetics (speech), and aesthetics (appearance). In addition to improving physiological function and aesthetics, complete dentures also improve the patient's quality of life and self-confidence. The success of complete denture treatment is greatly influenced by the accuracy of all clinical procedures, from diagnosis to the final stage of fitting. Another crucial factor is good cooperation between the dentist, dental technician, and patient. Effective communication and patient compliance with post-treatment instructions are crucial determinants of the long-term success of complete dentures.